111k views
5 votes
Use basic trigonometric identities to simplify the expression: sin^3 (x) + cos^2 (x) sin (x)

Use basic trigonometric identities to simplify the expression: sin^3 (x) + cos^2 (x-example-1

1 Answer

5 votes

Given the following trigonometric expression:


sin^3x+cos^2x*sinx=?

We will simplify the expression as follows:

First, taking sin (x) as a common


=sin\text{ }x*(sin^2x+cos^2x)

Second, we will use the following trigonometric identity:


sin^2x+cos^2x=1\rightarrow(1)

Finally, substitute the trigonometric identity number (1) into the given expression


=sin\text{ }x*1=sin\text{ }x

So, the answer will be sin (x)

User Joseph Jaquinta
by
4.7k points